KADAR AIR DAN NILAI pH PINDANG TONGKOL TERAWETKAN SERBUK BIJI PICUNG (Pangium edule Reinw) DAN GARAM SELAMA PENYIMPANAN: Moisture content and pH Boiled Salted Tuna Preserved by Picung Seeds Powder (Pangium edule Reinw) during Storage - Yuvita Lira Vesti Arista, Yuli Witono, Mukhammad Fauzi (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2021)
Boiled salted tuna is one of the processed fish products that are very popular with the public but has a relatively short shelf life. Therefore, this research was conducted to extend the shelf life of boiled salted tuna by adding picung seed powder (Pangium edule Reinw) (3% and 5%) and salt at various concentrations (15% and 20%). Boiled salted tuna was made using tuna with a weight range of ±200 g and picung seed powder was made using the freeze-dried method. Observations were made during storage on days 0, 3, 6, and 9 days covering moisture content and pH values. The results showed that the addition of picung seed powder at a concentration of 5% (P5) and the use of salt at a concentration of 20% (G 20) was considered to be able to maintain the quality of boiled salted tuna in terms of moisture content and pH value until the 9th day of storage.